Financial services law and compliance in Australia - Pearson, Gail (Cambridge University Press, 2009)
Up until the global credit crisis in 2008, 'Financial Services' was the fastest growing sector of the Australian economy. This growth has had profound implications for individuals, corporations and government. Following extensive review in the last part of the twentieth century, Australia put in place an overarching system for regulating all financial services, replacing a system that was based on separate regulation of products in individual industries. Focusing on the implications of the new system for retail clients - 'financial citizens' - Financial Services Law and Compliance in Australia provides a comprehensive account of the regulatory structure and a detailed analysis of the legislative framework, including discussion of the new regulatory bodies, the new licensing requirements for those wishing to enter the financial services market and the new obligations for those marketing or offering financial services to the public. This is an essential resource for those working in, and advising on, financial services, for students of financial services law, and for anyone needing to understand this new regime in Australia